Konstruksi Hukum Penetapan Calon Terpilih Anggota Dewan Perwakilan Rakyat oleh Komisi Pemilihan Umum di Indonesia (SETARA : Jurnal Ilmu Hukum, 2022)
The purpose of this paper is to explain legal certainty regarding the determination of elected candidates for members of the House of Representatives and legal protection for candidates who obtain the highest votes in general elections but are not determined as elected candidates by the General Election Commission. This study uses normative juridical legal research. The results describe the legal certainty of determining elected candidates for members of the House of Representatives under Law Number 7 of 2017 concerning General Elections and the legal protection for candidates who receive the highest votes but are not determined as elected candidates by the General Election Commission. In the 2019 election, the determination of elected candidates became a legal problem because the process of determining Gerindra Party candidates for the House of Representatives was considered inconsistent with election law following the South Jakarta District Court Decision Number 520/Pdt.Sus.Parpol/2019/PN.Jkt.Sel.
Keywords: Legal Certainty; Legal Protection; Determination of Elected Candidates; General Elections; House of Representatives